Quantificação de compostos fenólicos, poder antioxidante e teor de açúcares em produtos comerciais a base de Camellia sinensis L. - Thássia Fernandes Santana de Macena; Daiara Rakeli Simão Boyarski; Denise Rocha Ramos Barbosa; Rodolfo Castilho Clemente (Universidade do Estado do Rio de Janeiro, 2020)
Objective: To analyze and quantitatively compare phenolic compounds, antioxidant capacity and sugars present in infusions and soluble extracts of Camellia sinensis L, Methods: The study presents a completely randomized design, using samples for convenience, Three random samples of each type of tea, The analyzes of total phenolic compounds and flavonoids were determined by the Folin-Ciocalteu colorimetric method and aluminum chloride, respectively, total tannins by complexation with casein and condensates by the butanol-HCl method, The antioxidant capacity, by ferricyanide methodology and free radical scavenging by the radical 2,2-diphenyl-1-picryl-hydrazil, and reducing and non-reducing sugars, through the reagent 3-5 dinitrosalicylic acid, Result: The infused extracts showed significantly higher amounts of total phenolic compounds and flavonoids compared to the soluble, This behavior was the same for tannins and antioxidant activity, The infusions obtained greater reducing power and capacity to reduce free radicals, Soluble extracts were highlighted, with a greater presence of sugars, These results were confirmed by the literature and there were no studies carried out with soluble extracts and methodologies similar to that performed here for comparison, Conclusion: The infusions studied in the present study were richer in bioactive and antioxidant compounds, favoring their benefits for the population, with soluble extracts having a greater presence of additional sugars